(untitled) (Global Journal of Human-Social Science, 2025)
Bangladesh is among the most disaster-prone nations in the world right now The fact that it is the world s most densely inhabited nation makes the situation worse This article aims to analyze the role of print media during disaster period and how they use frames on it The study was conducted in the four selected newspapers of Dhaka city By using framing theory and qualitative approach of research it is focused on the presentation of disaster news coverage in the time of cyclone Mokha 2023 Findings show that newspapers use different types of frames and Bangla newspapers are more serious about cyclone Mokha than English newspapers The print media has become more powerful than before so how they are serving the country in a disaster situation it is viewed here It concludes with strong documents and examples that print media is very concern about natural disasters and they try to collect all information for the society and its people